How the Japanese Teacher Preparation Programs for Secondary Teachers Have Been Shaped Since the Meiji Period - Takeyu Ueyama (Comparative Education Society of Iran ( CESIR), 2019)
Japan took the initiatives to build the modern school system in 1872. The process of the building is characterized as the words like rapid, sometimes bold, and often tumbling in the economy, internal and external political conflicts and ideological conflicts.  It is not difficult to realize how various values and beliefs have been intervening in the process, but not easy to lucidly observe them.  The purpose of this study is to rediscover the cultural values and beliefs affecting the directions of teacher preparation programs for secondary school teachers in Japan.  This study is a qualitative study, mainly analyzing the historical studies done by other researchers. It examined the development of teacher preparation programs from the late 19th century to the present day.   Two different aspects were adapted for analysis: The concept of 'program' developed by Ueyama (2009), and the historical functions of university defined as organization, institution and community (Gamage & Ueyama, 2012).  This study discussed in the four areas of development of the teacher preparation programs: national policy, preparation at the university level, the program structure and content, and quality teacher.  It concluded what values were underlined and by what and how they were influenced in the process of shaping the teacher preparation for secondary school teachers.